Pars Plana Vitrectomy with Internal Limiting Membrane Peeling in Traumatic Macular Hole: 14% Perfluoropropane (C3F8) versus Silicone Oil Tamponade - Ashraf Bor’i; Mahmoud A. Al-Aswad; Ahmed Abdelwahab Saad; Dina Hamada; Ashraf Mahrous (Journal of Ophthalmology)
Purpose. To evaluate the outcome of 23 G PPV and ILM peeling with 14% C3F8 compared with silicone oil tamponade in cases of TMHs without spontaneous closure. Methods. A retrospective comparative study included 33 eyes with TMHs; 7 eyes healed spontaneously, and the remaining 26 eyes have been treated with PPV and ILM peeling. Silicone oil was used as a tamponade for children or adults who refused to adopt face-down position (10 cases). In all other cases (16 cases), 14% C3F8 was used. These cases were followed up for 6 months postoperatively. Results. 26 cases (22 males and 4 females) were reviewed, including 10 cases treated with silicone oil and 16 cases treated with 14% C3F8. Patients’ age ranged from 9 to 54 years. The success rate was 90% in the silicone-filled (9/10) and 94% in the gas-filled (15/16) eyes. At 6 months, the mean BCVA was 0.3 ± 0.25 in the silicone group and 0.2 ± 0.13 in the gas group (p<0.05). Conclusions. Cases of TMHs should be observed for spontaneous closure. PPV with ILM peeling should be conducted for nonclosing cases. Gas and silicone oil tamponades are equally successful in anatomical and visual outcomes. This trial is registered with CTRI/2017/06/008765.